Effect of Profitability Ratios on Banking Capital Adequacy (Study at PT. Bank Rakyat Indonesia Tbk.) - Ade Irma Suryani (Publisher Cv. Inara, 2020)
The main function of a bank is based on banking law no. 7 of 1992 is as an intermediary institution. As an intermediary institution, banks must be able to maintain profitability ratios and capital adequacy ratios. This is because the capital adequacy ratio of a bank is an important benchmark for consumers or users of these banking services. The focus of this research is to determine how much influence the profitability ratio of a bank, namely the ratio of NIM, OEOI and ROE to the Bank's Capital Adequacy, namely the CAR variable. The research method used is quantitative analysis using multiple linear regression. The results showed that all profitability ratios had a simultaneous effect on bank capital adequacy. Meanwhile, for the individual effect, only the ROE variable has no effect, while the other variables, namely NIM and BOPO, have a partial effect on CAR.